Determine the levels and standards for testing flight time and shooting accuracy for youth handball players - Azeez Salman, Hardan (International Journal of Psychosocial Rehabilitation, 2020)
The scientific development at the present time has led to reliance on testing, measurement and evaluation, where they play an important role in developing programs, curricula, planning, organizing and evaluation processes in various fields of education in general and physical education in particular, as they help to identify the physical condition and level of the individual's motor skill, characteristics and mental and social characteristics. The variables (flight time and shooting accuracy) are the main pillar through which the player can perform the skill of shooting with handball in different circumstances or under the pressure of competitors or its performance in extremely difficult circumstances. The physical abilities of the handball player are embodied in the player's approaching speed and the ability to run The speedy enables him to participate quickly in defense, attack and speed of movement as "the sport of handball requires a high level of strength, speed and endurance, especially bearing speed, in addition to flexibility and agility in the case of correction."